Assessment of the Role of Mouse-Like Rodents Background Species in the Preservation of Arboviral Infections Agents in the Semi-Desert Zone of Saratov Zavolzhie - I. V. Kutyrev; E. A. Bil'ko; I. N. Sharova; T. Yu. Krasovskaya; V. N. Chekashov; A. N. Matrosov (Проблемы особо опасных инфекций, 2008)
The role of the background species of mouse-like rodents in the preservation of arboviral infections in the semi-desert zone of Saratov Zavolzhie was studied. Determined were the indices of their number in the near-water and anthropogenic biotopes, and arboviral infection rate in some species. Substantiated was high potential epidemic danger of the intrazonal biotopes as centers of formation of associated natural foci of arboviral infections.